2001
DOI: 10.1021/jp010411h
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Properties of a Self-Assembled Zinc Porphyrin Tetramer II. Time-Resolved Fluorescence Spectroscopy

Abstract: Excited-state kinetics of complexes of a functionalized zinc tetraphenylporphyrin (ZnTPP) derivative, zinc mono(4-pyridyl)triphenylporphyrin (ZnPyP) in toluene and polystyrene/toluene mixtures have been investigated by time-resolved fluorescence spectroscopy. In addition to the ∼2.0 ns monomer fluorescence lifetime, a ≈ 1.5 ns component was found by applying global analysis to the time-resolved fluorescence decay. The 1.5 ns component is assigned to a cyclic porphyrin tetramer [Part I], with a ≈ 1 ns rotationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 47 publications
0
34
1
Order By: Relevance
“…Polarization‐dependent TA measurements, which employ different polarizations of the pump and probe pulses, provide valuable insights into the previously mentioned ultrafast depolarization channel;20b, 24, 27 this channel is too fast to be elucidated by the TCSPC technique with the time resolution of approximately 50 ps. As opposed to PBI J‐aggregate systems, in which the transition dipole moments are placed parallel to each other, the helically organized nature of our aggregate system allows for a fast decay component in the time‐dependent transient absorption anisotropy (TAA) profiles, which is indicative of an EET process between the constituent units.…”
Section: Resultsmentioning
confidence: 99%
“…Polarization‐dependent TA measurements, which employ different polarizations of the pump and probe pulses, provide valuable insights into the previously mentioned ultrafast depolarization channel;20b, 24, 27 this channel is too fast to be elucidated by the TCSPC technique with the time resolution of approximately 50 ps. As opposed to PBI J‐aggregate systems, in which the transition dipole moments are placed parallel to each other, the helically organized nature of our aggregate system allows for a fast decay component in the time‐dependent transient absorption anisotropy (TAA) profiles, which is indicative of an EET process between the constituent units.…”
Section: Resultsmentioning
confidence: 99%
“…276 The electron transfer rate was found to be ~8 times faster than the analogous Zn(II)-porphyrin tetramers. 717,718 A self-assembled cyclic zinc chlorophyll tetramer exhibited an ultrafast intramolecular energy transfer rate as determined from femtosecond singlet-singlet annihilation and transient absorption anisotropy studies. 719 The cyclic tetramer upon excitation with 120 fs laser pulses yielded its lowest singlet excited state in which the rate of energy transfer was ~20 times faster than the tetramer in the ground state.…”
Section: Miscelleneousmentioning
confidence: 99%
“…Schaafsma and coworkers observed photoexcited energy migration among the neighboring porphyrin units with a rate of (26 ps) −1 in the porphyrin square array 26b 4 . 160,161 On the other hand, Wasielewski et al observed the photoexcited energy migration in a similar square array of pyridyl-appended chlorophyll 27. 85 The rate of energy-hopping in 27 4 was (1.3 ps) −1 , 20 times faster than that in 26b 4 (Scheme 56).…”
Section: Intrawheel Energy-hopping Related To a Light-harvesting Amentioning
confidence: 99%
“…Photoexcited energy migration in porphyrin square array 26b 4 and chlorophyll square array 27 4 . 85,160,161 Scheme 57. Macrocyclic wheels 42 and 114, synthesized using the template-directed method, incorporating tetrapyridylporphyrin as an electron acceptor and 115 as an energy acceptor.…”
Section: Multiporphyrin Wheel Incorporating a Light-energy Funnelimentioning
confidence: 99%